2012
DOI: 10.1007/s10620-012-2255-8
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin/NFATc1 Pathway Contributes to Cell Proliferation in Hepatocellular Carcinoma

Abstract: The calcineurin/NFATc1 signal is overexpressed and active in HCC. It may enhance the proliferative potential of HepG2 cells through transcriptional activation of the c-myc and cox-2 oncogenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 16 publications
0
52
0
Order By: Relevance
“…In contrast to the heart, where calcineurin and NFAT are components of an established pathway that regulates cardiac remodeling (56), little is known about the function of calcineurin/NFAT signaling in the liver (57, 58). Our study suggests that calcineurin/NFAT activation in hepatocytes induces an inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the heart, where calcineurin and NFAT are components of an established pathway that regulates cardiac remodeling (56), little is known about the function of calcineurin/NFAT signaling in the liver (57, 58). Our study suggests that calcineurin/NFAT activation in hepatocytes induces an inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Calcineurin (CaN) has been reported to be a possible candidate in the signaling of skeletal muscle cellular growth, and plays an important role in regulating cell proliferation34 and differentiation353637. CaN has also been reported to affect the muscle regeneration by association with NFATc1, a downstream target of CaN signaling37.…”
Section: Discussionmentioning
confidence: 99%
“…Another study has shown that activation and nuclear translocation of NFAT2 (also known as NFATc1) are increased in proliferating small cholangiocytes [45]. This Ca 2+ /CN/NFATc1 pathway is also associated with cell proliferation in hepatocellular carcinoma [46]. In large cholangiocytes, however, Ca 2+ signaling may not be critical for cell proliferation during cholestatic liver injury.…”
Section: Mechanisms Of Cholangiocyte Proliferation and Functionsmentioning
confidence: 99%